Recurrent Intussusception in Adolescence: A Rare Entity: Invaginação Recorrente na Adolescência: Uma Entidade Rara - Leitão, Cátia Vilas Boas; Tenente, Joana; Ribeiro, Andreia; Pinto Pais, Isabel (Gazeta Médica, 2020)
A healthy 16-year-old male presented to the emergency department with vomiting and pain in the right iliac fossa for the previous 12 hours, with no other symptoms.